On the structural, magnetic and electrical properties of sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2009)
Nanoparticles of cobalt ferrite were synthesized by sol gel method. These particles were structurally characterized by using X-Ray Diffraction and Transmission Electron Microscopy, High Resolution Transmission Electron Microscopy, Energy Dispersive Spectrum and Inductively Coupled Plasma Analysis and the results confirmed the formation of spherically shaped nanoparticles of cobalt ferrite having a size lying in the range of 13-14 nm. The as prepared sample was sintered at 800 degrees C and the structural, magnetic and dielectric properties were measured. The dielectric properties were studied and analyzed as a function of temperature and frequency. The ac and dc conductivity studies were carried out to delve into the conduction mechanism. The existing models based on quantum mechanical tunneling were effectively employed to explain the frequency dependent conductivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic Transport; Magnetic measurements; Magnetically ordered materials; Nanostructures; Scanning and transmission electron microscopy; Sol-gel synthesis; X-ray diffraction

Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction

Magnetic properties of thermal plasma synthesized nanocrystalline nickel ferrite (NiFe2O4) - Nawale, Ashok B.; Kanhe, Nilesh S.; Patil, K. R.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Journal of Alloys and Compounds, 2011)
A rapid synthesis method is reported for magnetic nanoparticles of nickel ferrite involving thermal plasma assisted vapor phase condensation process. The as-synthesized samples were characterized by X-ray Diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and X-ray Photoelectron Spectroscopy techniques. The average particle size was determined from the TEM micrographs and found to be around 30 nm. The effects of reactor parameters on the magnetic and structural properties have been evaluated, to find the optimized parameters so as to achieve the highest values of saturation magnetization and coercivity. Reasonably high saturation magnetization (48 emu/g) has been assigned to the high degree of crystallinity, achieved on account of high temperature during the growth, and the cation redistribution. The high value of coercivity (1150e) is explained on the basis of possible lattice defects arising from the cation redistribution. Detailed analysis of cation distribution using the XRD line intensity data leads to the conclusion that these samples are iron deficit and nickel rich. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic measurements; Magnetization; Nanostructured materials; TEM

Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B. P.; Sharma, Geeta; Sharma, Preeti (Ceramics International, 2020)
Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz. 297 cm(-1) -302 cm(-1), 473 cm(-1)-475 cm(-1), 516 cm(-1) -524 cm(-1) and 729 cm(-1) -733 cm(-1) in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, T c close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.
Keywords: BCT; dielectric response; Fe doping; ferroelectric properties; Lead free ceramics; Magnetic measurements